Global Excision of Severe Heterotopic Ossification of the Shoulder: A Case Report. Issue 1 (January 2020) - Polfer, Elizabeth M.; Nappo, Kyle E.; Giuliani, Jeffrey R.; Nesti, Leon J.
Abstract : Case: A 21-year-old man sustained a closed glenohumeral fracture/dislocation as a pedestrian struck by a motor vehicle. He was treated nonoperatively and developed severe post-traumatic heterotopic ossification (HO) with near-complete shoulder ankylosis. We present our technique for safe surgical excision. Conclusions: Excision led to improvements in motion and quality of life at 1 year postoperatively. Recommendations for successful HO excision around the shoulder include excision after at least 180 days, appropriate preoperative imaging to include cross-sectional imaging and a 3D model, intraoperative fluoroscopy, well-serviced instruments, preparation for iatrogenic fracture and/or neurovascular injury, meticulous hemostasis, postoperative HO prophylaxis, immediate postoperative therapy, and involvement of a multidisciplinary team.